Apostolos Sarris (ed.). Best practices of geoinformatic technologies for the mapping of archaeolandscapes - Gaffney, Chris (Journal of Greek Archaeology, 2016)
This edited volume is a product of the POLITEIA project / Action KRIPIS funded by the Ministry of Education, Greece and the European Regional Development Fund / European Commission and contains 25 articles of varying length and scope. It is evident from the title of the volume that there is a theme running through the articles that draws on concepts relating to best practice in a variety of geoinformatic technologies. Furthermore, the imagery and case studies that populate the pages of the volume are familiar to those with an interest in Greek archaeology, or the broader Mediterranean zone.